Standardized seed extract of Cajanus cajan (L) Millsp. produced antinociceptive and anti-inflammatory actions through inhibition of inflammatory mediators and activation of opioidergic signaling - Taiwo G. Olubodun-Obadun; Ismail O. Ishola; Chisom A. Osumuo; Olufunmilayo O. Adeyemi (Elsevier, 2023)
Background and Purpose: Peripheral tissue damage and diseases could lead to persistent pain beyond possible resolution suggestive of disease-promoting condition which gives rise to chronic pain. The inability of current medications to manage some chronic inflammatory and painful conditions necessitate the need for better treatment options. Natural products have been a veritable source for the discovery of more efficacious and safer therapeutics. Cajanus cajan (L) Millsp, (Fabaceae) is used in traditional African medicines for the treatment of painful, gut disturbance and inflammatory conditions. Hence, the current study aims to investigate the anti-inflammatory and antinociceptive actions of the ethanol seed extract of Cajanus cajan (CC) in rodents and possible mechanisms of action. Methods: High performance liquid chromatography coupled with diode-array detection (HPLC-DAD) was used to identify 8 major flavonoids in CC. Antinociceptive activity was investigated using the acetic acid-induced writhing reflex, biphasic formalin-induced flinching behaviour and supraspinal hot plate-evoked nociception in mice. Carrageenan-induced rat paw oedema test was used to evaluate the anti-inflammatory action of CC in rats. Possible mechanism of antinociception and anti-inflammatory actions were examined using both in vivo model and molecular docking procedures against µ-opioid receptor (MOR), cyclooxygenase-2 (COX-2) and phospholipase A2 (PLA2) proteins, respectively. Results: The chromatographic procedure qualitatively and quantitatively confirmed the presence of rutin, quercetin, gallic acid, luteolin, pinostrobin, BiochaninA, formononetin and apigenin in CC. The in vivo nociceptive assay, showed that CC (50, 100, or 200 mg/kg, p.o.) significantly decreased mean number of writhing reflex with peak effect at 50 mg/kg (72% inhibition) when compared with vehicle control in mouse writhing test. Similarly, the biphasic formalin-induced nociception was significantly reduced by CC (50 mg/kg) with 24.61 and 66.73% inhibition of nociceptive reactions in both the early and late phases of formalin-induced inflammatory pain, respectively. In addition, CC significantly increased supraspinal thermally mediated pain threshold with maximum possible effects of 42.25 and 52.16% at CC 50 and 100 mg/kg, respectively, in hot-plate test. Similarly, CC100mg/kg caused time course inhibition of carrageenan-induced paw oedema in rat with peak effect (65.78%, CC 100 mg/kg; 6 h). Interestingly, the antinociceptive action of CC was blocked by the pre-treatment of mice with l-NG-nitro arginine methyl ester (L-NAME) or naloxone. The molecular docking analysis revealed prominent interactions of pinostrobin, physcion and lupeol with MOR, COX-2, and PLA2, respectively. Conclusion: Findings from this study showed that Cajanus cajan seeds extract possesses anti-nociceptive and anti-inflammatory through inhibition of inflammatory mediators (PLA2/COX-2) and activation of opioidergic signalling.